Perancangan Interior The House of Jhony Salon & Bridal di Surabaya - Shierly Susanto; mariana wibowo; Diana Thamrin (Intra, 2016)
Marriage is one of the most important event in life that only happens once in a lifetime. Marriage has many preparations and can’t be planned in a short period of time. Vendors provided has many variety of options and the distance is not near, so be very inconvenient for the bride and groom. Therefore needs a place that can accommodate the entire wedding preparation facilities in one area. The brand which is used is Jhony salon & bridal because it has reliable quality and has many MURI awards. By using The Perfect Blend concept, it is expected to feel comfortable, elegant, and sacred so everything about the wedding can be prepared perfectly.